Preparation and Characterization Evaluation The Zno Nanoparticles on Lymphocyte Vitality: Persiapan dan Evaluasi Karakterisasi Nanopartikel Zno pada Vitalitas Limfosit - Lateff, Nedhal Ibrahim; Al-Obaidi, Fiham Jassim; Hameed, Ashwaq Talib; Saleh, Eman Naji (Universitas Muhammadiyah Sidoarjo, 2024)
The oxidase-positive, motile, Gram-negative bacteria Plesiomonas shigelloides is found all across the natural world. Additionally, it is a major pathogen that mostly causes disorders of the intestines in humans. Most of these illnesses are characterised by diarrhoea, which may be watery, invasive, or chronic in nature. There have been reports of intestinal illnesses caused by Plesiomonas that were spread by food and water. There are a number of extraintestinal diseases caused by P. shigelloides, the most prevalent of which are sepsis and meningitis, both of which are associated with significant fatality rates. Phylogenetically closely related to other Enterobacteriaceae species, P. shigelloides differs biochemically from them. A single biovar, with over a hundred serovars documented. Some have proposed P. shigelloides as a